A Commognitive Perspective: How Visual, Auditorial, and Kinesthetic Learners Solve Linear Programming Problem? - Rolanza .; Rita Lefrida; Pathuddin .; Alfisyahra . (Didaktik Matematika, 2025)
This study aims to explore students' commognitive processes in solving linear programming problems based on their learning styles. Conducted with three female students from Class XI MIPA 4 at SMAN 5 Palu, the study included one student each with visual, auditory, and kinesthetic learning styles. Data collection involved administering a learning style questionnaire and linear programming tasks (SBMPTN 2014 Code 663) that were linguistically validated to suit the students in Palu. Interviews were also conducted while the students worked on these tasks. Results indicate that the visual learner responded to problems in a detailed, repetitive, efficient, and accurate manner, demonstrating all four commognitive indicators. The main finding was the student's clear process in visualizing the problem. The auditory learner also responded well, demonstrating the four commognitive indicators but faced difficulties in the routine aspect, especially in transforming the problem into a narrative form, which is crucial for problem-solving. The kinesthetic learner showed clear, accurate responses and exhibited all four commognitive indicators, with a notable habit of using finger-pointing during explanations. However, limitations were observed in the narrative aspect, where the student relied more on physical experience than on logical, in-depth explanation.